Left lateral segment pediatric liver transplantation: a 25 year experience at Mount Sinai. Issue 6 (June 2022) - Tabrizian, Parissa; Holzner, Matthew L.; Adamson, Dylan; Balci, Deniz; Jung, Yun K.; Arnon, Ronen; Chu, Jaime; Emre, Sukru; Facciuto, Marcelo; Schwartz, Myron; Moon, Jang; Iyer, Kishore; et al.
Abstract: Background: Outcomes of left lateral segment (LLS) grafts in pediatric recipients were compared between living (LD-LLS) and deceased donor (DD-LLS) grafts. Methods: 195 LLS grafts (99DD-LLS-96LD-LLS) were analyzed with a median follow-up of 9.1years. The primary endpoints were overall patient/graft survival. Results: LD-LLS grafts were younger (0.9vs.1.4years, p = 0.039), more likely to have a fulminant liver failure (17.9%vs.5.3%, p = 0.002), less likely to have a metabolic disorder (6.3%vs.25.5%, p = 0.002), and less likely to be undergoing retransplantation (5.3% vs.16.2%, p = 0.015). There was a trend toward decreased hepatic artery thrombosis in LD-LLS grafts (6.6% vs. 15.5%, p = 0.054). No differences in the overall biliary complications occurred. The LD-LLS group had prolonged survival compared to the DD-LLS group with 10-year survival rates of 81%, and 74% (p = 0.005), respectively. LD-LLS grafts had longer graft survival compared to DD-LLS grafts (10-year graft survival 85%vs.67%, p = 0.005). Recipient age >1year (HR 2.39, p = 0.026), aortic reconstruction (HR 2.12, p = 0.046) and vascular complication (HR 3.12, p < 0.001) were independent predictors of poor patient survival. Non-biliary liver disease (HR 2.17, p = 0.015), DD-LLS (HR 2.06, p = 0.034) and vascular complication (HR 4.61, p < 0.001) were independent predictors of poor graft survival. Conclusion: The use of SLT remains a viable option with excellent long-term outcomes. We show improved graft and patient survival with living donor grafts.